Prumnopitys Andina Fruit Extract Activates Liver X Receptors after In Vitro Digestion. Issue 1 (16th November 2022) - Jiménez‐Aspee, Felipe; Pospiech, Jonas; Bauer, Sarah; Sus, Nadine; Kufer, Thomas A.; Frank, Jan
Abstract : Scope: 20‐Hydroxyecdysone (20E) is the main phytochemical present in the fresh arils of Prumnopitys andina . 20E is reported to have anabolic effects by modulation of gene transcription by interaction with nuclear receptors. Our aim is to evaluate the in vitro bioaccessibility, transepithelial transport of 20E, and the capacity of P. andina fruit extract and 20E to activate selected mammalian nuclear receptors in transiently transfected human cells after simulated gastrointestinal digestion. Results: 20E shows good stability, solubility, and micellization after in vitro digestion. 20E is taken up by Caco‐2 cells, but poorly transported through the epithelial cell membrane, possibly due to P‐glycoprotein‐mediated efflux. In transiently transfected HepG2 cells, the fruit extract significantly induces the signal intensity for the liver X receptor (LXR)‐α and ‐β by 1.6 and 1.4‐fold, respectively. In contrast, the treatment with 20E, irrespective of its concentration, did not change the activity of both LXR receptors. No effects are observed for the pregnane X receptor or the constitutive androstane receptor. Conclusion: Our findings show that components of the digested P. andina extract other than 20E are responsible for the effects on LXR‐α and ‐β. Our findings open new perspectives on the potential role of P. andina fruits in cholesterol metabolism and inflammatory diseases. Abstract : Phytoecdysteroids are a large group of steroids that are synthesized by plants as defense against insects. Numerous phytoecdysteroids have been identified in nature, and among them, 20‐hydroxyecdysone (20E) is the most common one in plants. Prumnopitys andina fruits are a rich source of 20E. The present study evaluates the bioaccessibility, transepithelial transport of 20E and the capacity of 20E and P. andina fruit extract to activate selected nuclear receptors in transiently transfected human cells after simulated gastrointestinal digestion.